Analisis Dampak Usaha Mikro Kecil Dan Menengah (UMKM) Terhadap Kesejahteraan Masyarakat : (Studi Pada Sentra Industri Kecil Roti Desa Kalimalang Kecamatan Sukorejo Kabupaten Ponorogo) - Muji Marwati; Muhammad Mudjib Musta’in; Humaidah Muafiqie (Universitas Darul Ulum, 2021)
Micro, Small and Medium Enterprises (MSMEs) are the spearhead and savior of the Indonesian economy. The purpose of this study is to analyze the pattern and analysis of the impact of SMEs in the small industrial center of Kalimalang bread on the welfare of the community in Kalimalang Village, Sukorejo, Ponorogo. This research is a field research where the authors look for data, research, review and make direct observations to 5 of 22 SMEs in small bread industry centers and employees in Kalimalang, Sukorejo, Ponorogo Villages and the data in this study were analyzed descriptively analytically. For the activities of Micro, Small and Medium Enterprises (MSMEs) of bread located in Kalimalang Village, it is known that in an effort to improve the welfare of the community they use a kinship pattern. Micro, Small and Medium Enterprises (MSMEs) of bread located in Kalimalang Village, have a positive impact on improving people's welfare as seen from the level of community income which has increased after the existence of bread MSMEs.